(untitled) (Hekima Review, 2015)
Violations of human rights the world over persist as a threat to people’s dignity. Such violations have likewise been a major stumbling block towards the achievement of the common good. The article develops a repertoire of responses to the problem which reflect hope for a bright and a more unified world in the future without gross human rights violations and deleterious conflicts. Methodologically, the article develops a moral narrative that responds to the problem by basing its argument on the four pillars of moral theology which include: 1) the Bible and Christian tradition, 2) philosophical approaches, insights and other fundamental principles, 3) scientific narratives and other methods that are enlightening, 4) and human experience as it is generally perceived.